The Open Library at AU (Athabasca University): supporting open access and open educational resources - Colin Elliott; Elaine Fabbro (Open Praxis, 2015)
To address challenges that learners, course creators, librarians and academics involved with OER and MOOCs are facing when looking for scholarly materials, Athabasca University Library has initiated the development of the Open Library at AU. This open library is a full library website that provides easy access to open and free resources. Tools and information literacy tutorials are also included to enable learners, researchers, and others to find, evaluate, and use the information they need for their open learning course or research. Many of the challenges that those involved in open learning face are addressed by the open library and the potential impact it can have on open learning and knowledge sharing is tremendous.